EVALUATION OF SERVICE STANDARDS IN THE INFORMATION AND COMPLIANCE SERVICE TAX OFFICE - Agus Bandiyono; Shanti Dwi Aryani (Dinasti International Journal of Education Management And Social Science, 2019)
This study aims to evaluate the service component standard of the Directorate General of Tax Information and Complaints Service Office and to identify the factors supporting the success of services at the Information and Information Services Office Complaints from the Directorate General of Tax. This study uses qualitative methods through interviews. The results show that there are several service standard components not included in the Information and Complaints Service Office's Standard Standards, namely cost/tariff requirements, infrastructure and/or facilities, implementing competencies, internal control, complaint handling, service guarantees, security guarantees, and performance evaluation executor. However, the Ministry of Finance has further stipulated which components must be included in the Standard Operating Procedures in the Regulation of the Minister of Finance of the Republic of Indonesia Number 131 / PMK.01 / 2015 concerning Guidelines for the Preparation of Business Processes, Decision Making Framework and Standard Operating Procedures in Ministry of Finance environment. Even though it does not meet the components in the Public Service Act it is not considered a problem as long as it fulfills the components in the PMK. Supporting factors for service success begins with determining Strategic Targets and Key Performance Indicators, then supported by activities needed to achieve the targets of each of the Key Performance Indicators.